Spacecraft Improves Understanding of Turbulent "Interface" Region of the Sun. (17th December 2013) - Showstack, Randy
Abstract : The region of the Sun between its surface and its outer atmosphere is even more violent and turbulent than had been expected and better knowledge about that little‐understood region could improve our understanding of space weather, scientists involved with NASA's Interface Region Imaging Spectrograph (IRIS) said at a 9 December briefing at the AGU Fall Meeting in San Francisco, Calif.